GAMBARAN KADAR HEMOGLOBIN PADA MAHASISWI - Tanggo, Gerald; Wowor, Mayer Ferdinand; Berhimpon, Siemona L. E. (Universitas Sam Ratulangi, 2026)
Background: Overweight and obesity are health problems commonly found among female university students. These conditions may be associated with physiological changes such as low-grade chronic inflammation, which can affect iron metabolism through increased hepcidin levels and potential iron restriction. In females, hemoglobin (Hb) levels may also be influenced by menstrual patterns, dietary habits, physical activity, and stress levels. To date, data describing hemoglobin levels among overweight and obese female students at the Faculty of Medicine, Sam Ratulangi University, remain limited. Objective: To describe hemoglobin levels among overweight and obese female students of the Medical Education Study Program, Class of 2024. Methods: This was a descriptive study with a cross-sectional approach. Samples were obtained using purposive sampling, resulting in 30 female students who met the inclusion and exclusion criteria. Results: Most participants in both groups had hemoglobin levels within the normal range. Among the overweight participants, 86.7% had normal hemoglobin levels and 13.3% had low hemoglobin. Similarly, among the obese participants, 86.7% had normal hemoglobin levels and 13.3% had low hemoglobin. Conclusion : The majority of samples with overweight and obesity each had normal hemoglobin levels. Keywords: BMI ; Female Sudents ; Hemoglobin